Brugada Phenocopy Type 1 Secondary to Synthetic Cannabinoids - Mohammad Amro; Kelechukwu U. Okoro; Kanaan Mansoor; Ahmed Amro; Paul Okhumale (Case Reports in Cardiology)
Brugada phenocopies (BrP) are clinical entities that have EKG tracings similar to the congenital Brugada syndrome (BrS) but without ventricular tachyarrhythmias or sudden cardiac death. BrP is caused by various factors such as metabolic disturbances (electrolyte imbalance), drugs, mechanical compression of the mediastinum, and inflammatory conditions such as myocarditis or pericarditis. We present a very rare case of a young patient who had a Brugada phenocopy Type 1 suspected to be secondary to synthetic cannabinoids.